2021
DOI: 10.4142/jvs.2021.22.e51
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of ovine herpesvirus-2 using heminested PCR in Pakistan

Abstract: Background Malignant catarrhal fever (MCF) is a highly fatal lymphoproliferative disease of cattle, deer, bison, water buffalo, and pigs caused by the gamma-herpesviruses alcelaphine herpesvirus-1 (AlHV-1) and ovine herpesvirus-2 (OvHV-2). Objectives This study aimed to determine the prevalence of OvHV-2 in sheep, goats, cattle, and buffalo in Rawalpindi and Islamabad, Pakistan, by applying molecular and phylogenetic methods. Methods Blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Based on the results of BLAST and phylogenetic analysis, the sequences obtained in this study showed approximately 98-100% similarity to other published sequences of the ORF75 tegument protein gene internationally. These ndings support other researchers' ndings that there is no major difference between OvHV-2 sequences globally [14,19,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on the results of BLAST and phylogenetic analysis, the sequences obtained in this study showed approximately 98-100% similarity to other published sequences of the ORF75 tegument protein gene internationally. These ndings support other researchers' ndings that there is no major difference between OvHV-2 sequences globally [14,19,31].…”
Section: Discussionsupporting
confidence: 91%
“…Goats are natural hosts of caprine herpesvirus 2 (CpHV-2) [2,25]. However, as we detected OvHV-2 in this study, some evidence indicates that goats are reservoir hosts for OvHV-2 [17,19,26,27], because mixed farming is common in this region, OvHV-2 may be transmitted between sheep and goats without any speci c clinical signs. However, some studies have suggested that OvHV-2 can lead to subclinical infection in goats as well as exhibit clinical signs, such as fever and central nervous system disorders, such as ataxia and head tremors [28,29].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Sheep-associated MCF occurs worldwide, and immunosuppression factors are necessary as precursors of this form [ 33 ]. A cross-sectional study on the prevalence and molecular detection of OvHV-2 in apparently healthy buffalo in Pakistan confirmed that they could be carrying OvHV-2 acquired from OvHV-2-positive sheep and goats [ 34 ].…”
Section: Malignant Catarrhal Fevermentioning
confidence: 99%